Introducing rapid tests for malaria into the retail sector: what are the unintended consequences?. Issue 1 (11th January 2017) - Hutchinson, Eleanor; Hutchison, Coll; Lal, Sham; Hansen, Kristian; Kayendeke, Miriam; Nabirye, Christine; Magnussen, Pascal; Clarke, Siân E; Mbonye, Anthony; Chandler, Clare I R
Abstract : The observation that many people in Africa seek care for febrile illness in the retail sector has led to a number of public health initiatives to try to improve the quality of care provided in these settings. The potential to support the introduction of rapid diagnostic tests for malaria (mRDTs) into drug shops is coming under increased scrutiny. Those in favour argue that it enables the harmonisation of policy around testing and treatment for malaria and maintains a focus on market-based solutions to healthcare. Despite the enthusiasm among many global health actors for this policy option, there is a limited understanding of the consequences of the introduction of mRDTs in the retail sector. We undertook an interpretive, mixed methods study with drug shop vendors (DSVs), their clients and local health workers to explore the uses and interpretations of mRDTs as they became part of daily practice in drug shops during a trial in Mukono District, Uganda. This paper reports the unintended consequences of their introduction. It describes how the test engendered trust in the professional competence of DSVs; was misconstrued by clients and providers as enabling a more definitive diagnosis of disease in general rather than malaria alone; that blood testing made drug shops more attractive places to seek care than they had previously been; was described as shifting treatment-seeking behaviour away from formal health centres and into drug shops; and influenced an increase in sales of medications, particularly antibiotics. Trial registration number: NCT01194557 ; Results.